Multikultural Education’s Concept and It’s Value In The Qur’an - Fadlan, Amul Husni; Lutfiyani, L; Yahya, Nur Edi Prabha Susila (Prosiding University Research Colloquium, 2018)
Basically, Multikultural’s education is not contradict with the teaching of Islam especially Qur’an which becomes the source of law in Islam. The diversity is actually becomes the rich of intelectual’s wealth for reviewed. As it is in some verses of Qur’an which explains about that. Hoefully with the existence of multikultural’s education, every individual or group should be expected to receive and appreciate many differences, they live together with peace and prosperous. This writing will discuss about the multikultural’s education concept and the education’s value in the Qur’an. Therefore, the writer try to find the information to replied that problems, through the study exegis of interpretation the verses in Qur’an which is relevant the problems. This study has some goals, aimed to anaylyze: 1. The multikultural’s education concept based on the thought of some education’s expert, 2. To know the multikultural’s education vales which can be found in Qur’an, 3. Multikultural’s education urgency in contemporary Islamic education, nowadays. From the end of study, it can be conclude that: multikultural’s education is not contradict with the teaching of Islam. More over the multikultural’s education are also found in Qur’an. For example are learning to live in the diversity, buliding the mutual trust and mutual understanding, mutual respect, openminded in thinking, appreciation and interdependency, confilct’s resolution and reconciliation.